The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1038/s41598-020-60761-5
|View full text |Cite
|
Sign up to set email alerts
|

TREM-1 activation is a potential key regulator in driving severe pathogenesis of enterovirus A71 infection

Abstract: Hand, foot and mouth disease (HFMD), caused by enterovirus A71 (EV-A71), presents mild to severe disease, and sometimes fatal neurological and respiratory manifestations. However, reasons for the severe pathogenesis remain undefined. To investigate this, infection and viral kinetics of EV-A71 isolates from clinical disease (mild, moderate and severe) from Sarawak, Malaysia, were characterised in human rhabdomyosarcoma (RD), neuroblastoma (SH-SY5Y) and peripheral blood mononuclear cells (PBMCs). High resolution… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 72 publications
(70 reference statements)
0
5
0
Order By: Relevance
“…Thus, it appears that the ability of EV-A71 to manipulate its host immune system represents an integral part of its virulence strategy, and influences the clinical outcome. However, while some recent evidence support that EV-A71 strains associated with severe clinical outcome manipulate differently their host immune signalling pathways [ 64 ], the viral determinants involved have yet to be reported.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Thus, it appears that the ability of EV-A71 to manipulate its host immune system represents an integral part of its virulence strategy, and influences the clinical outcome. However, while some recent evidence support that EV-A71 strains associated with severe clinical outcome manipulate differently their host immune signalling pathways [ 64 ], the viral determinants involved have yet to be reported.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…Amrun et al. reported that severe EV-A71 infection leads to activation of the TREM-1 signaling pathway, and LP17-mediated TREM-1 inhibition does not affect the replication of EV-A71 ( 27 ). Herein, we investigated whether the LP17-mediated down-regulation of the TREM-1 signal pathway affects the replication of EV-D68.…”
Section: Resultsmentioning
confidence: 99%
“…However, fever was not the most common sign among patients with COVID-19 in our cohort, especially in cases of mild and moderate disease. While the role of sTREM-1 in patients presenting severe COVID-19 remains unclear, a functional genomic analysis of PBMCs from individuals undergoing infection with enterovirus A71 (EV-A71) determined that activation of TREM-1 was correlated with clinical severity [35]. Interestingly, genetic variants within the gene encoding TREM-1 are associated with different levels of inflammation and with the development of sepsis [36] and severe malaria in which sTREM-1 levels were high [8].…”
Section: Discussionmentioning
confidence: 99%